Mevlana'nın Mesnevi'sinin Tamamına Yapılan Türkçe Şerhler - Güleç, İsmail (Gökkubbe, 2006)
Mesnevî'nin tamamı yazıldığı tarihten bu yana sekiz kez şerh edilmiştir. Bunlardan dördü muhtasar dördü de mufassaldır. Mesnevi şarihlerinin altısı Mevlevi iken ikisi farklı tarikatlara mensuptur. Bu çalışmada bu şerhler hakkında bilgi verilmiş ve mukayesesi yapılmıştır. Eight commentaries were written on Mawlana's Masnawi since it had been written. Four of them are considered as brief commentaries, and others are detailed. Whereas the six of Masnavi commentators were connected to Mewlevi order, the others were connected to different orders. In this article, information about these commentaries is given and compared.
The Turkish Commentaries Written on Whole of Mevlana's Masnawi
Keywords: Mevlana; Mesnevi; Şerhler; Şarihler; Commentary; Commentators